Multiomics and spatial mapping characterizes human CD8+ T cell states in cancer - Naulaerts, S; Datsi, A; Borras, DM; Antoranz Martinez, A; Messiaen, J; Vanmeerbeek, I; Sprooten, J; Laureano, RS; Govaerts, J; Panovska, D; Derweduwe, M; Sabel, MC; et al. (American Association for the Advancement of Science, 2023)
Clinically relevant immunological biomarkers that discriminate between diverse hypofunctional states of tumor-associated CD8+ T cells remain disputed. Using multiomics analysis of CD8+ T cell features across multiple patient cohorts and tumor types, we identified tumor niche–dependent exhausted and other types of hypofunctional CD8+ T cell states. CD8+ T cells in “supportive” niches, like melanoma or lung cancer, exhibited features of tumor reactivity–driven exhaustion (CD8+ TEX). These included a proficient effector memory phenotype, an expanded T cell receptor (TCR) repertoire linked to effector exhaustion signaling, and a cancer-relevant T cell–activating immunopeptidome composed of largely shared cancer antigens or neoantigens. In contrast, “nonsupportive” niches, like glioblastoma, were enriched for features of hypofunctionality distinct from canonical exhaustion. This included immature or insufficiently activated T cell states, high wound healing signatures, nonexpanded TCR repertoires linked to anti-inflammatory signaling, high T cell–recognizable self-epitopes, and an antiproliferative state linked to stress or prodeath responses. In situ spatial mapping of glioblastoma highlighted the prevalence of dysfunctional CD4+:CD8+ T cell interactions, whereas ex vivo single-cell secretome mapping of glioblastoma CD8+ T cells confirmed negligible effector functionality and a promyeloid, wound healing–like chemokine profile. Within immuno-oncology clinical trials, anti–programmed cell death protein 1 (PD-1) immunotherapy facilitated glioblastoma’s tolerogenic disparities, whereas dendritic cell (DC) vaccines partly corrected them. Accordingly, recipients of a DC vaccine for glioblastoma had high effector memory CD8+ T cells and evidence of antigen-specific immunity. Collectively, we provide an atlas for assessing different CD8+ T cell hypofunctional states in immunogenic versus nonimmunogenic cancers.